Resistance and virulence potential of uropathogenicEscherichia colistrains isolated from patients hospitalized in urology departments: a French prospective multicentre study. Issue 6 (June 2016) - Lavigne, Jean‐Philippe; Bruyère, Franck; Bernard, Louis; Combescure, Christophe; Ronco, Esthel; Lanotte, Philippe; Coloby, Patrick; Thibault, Michel; Cariou, Gérard; Desplaces, Nicole; Costa, Pierre; Sotto, Albert
Abstract : N/A: We characterized antibiotic resistance and virulence of uropathogenic Escherichia coli (UPEC) strains isolated from urinary tract infections (UTIs) in patients hospitalized in urology departments. A prospective multicentre study was initiated from March 2009 and lasted until February 2010 in French urology units. All patients with asymptomatic bacteriuria (ABU), acute cystitis, acute pyelonephritis or acute prostatitis in whom UPEC was detected were included. Antimicrobial resistance and virulence factors were compared among the different groups. To identify independent associations between virulence markers and the risk of UTI, we used a multivariate logistic regression. We included 210 patients (mean age: 65.8 years; 106 female). Episode of UTI was community acquired in 72.4 %. ABU was diagnosed in 67 cases (31.9 %), cystitis in 52 cases (24.7 %), pyelonephritis in 35 cases (16.7 %) and prostatitis in 56 cases (26.7 %). ABU was more frequent in patients with a urinary catheter (76.1 vs 23.9 %, P <0.001). The resistance rate was 7.6 and 24.8 % for cefotaxime and ciprofloxacin, respectively. UPEC isolated from infections belonged more frequently to phylotypes B2 and D ( P =0.07). The papG allele II and papA, papC, papE, kpsMTII and iutA genes were significantly more frequent in infecting strains ( P <0.05). In multivariate analysis, strains susceptible to ciprofloxacin were significantly associated with papG allele II ( P =0.007), kpsMTK1 ( P <0.001) and hlyA ( P <0.001) compared with the ciprofloxacin‐resistant strains. To the best of our knowledge, this is the first study evaluating the antibiotic resistance and virulence features of UPEC isolated from patients hospitalized in urology departments. High resistance rates were observed, notably for ciprofloxacin, highlighting the importance of a reinforced surveillance in this setting.